2023
DOI: 10.20344/amp.19048
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Psoriasis in Portugal: A Population-Based Study

Abstract: Introduction: Psoriasis is a common, chronic, and inflammatory skin disorder with a high personal, social and economic burden and important implications for healthcare systems. The aim of this study was to provide an epidemiological characterization of individuals with psoriasis in Portugal.Material and Methods: A large observational, cross-sectional, nationwide, population-based survey study developed by the Portuguese Psoriasis Group of the Portuguese Society of Dermatology and Venereology (GPP-SPDV). A stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our study found a slightly higher decrease in ASPR and ASIR in females between 2019 and 1990, while similar changes in ASDR were observed between both genders. Most studies found in the literature reported higher rates of prevalence and incidence in males than females [28][29][30][31][32][33][34], while other studies reported no differences between males and females [24,[35][36][37], and some described that females had higher incidence and prevalence [35,38,39]. The disparities in reported rates between males and females in various studies may be due to varying risk factors distributions between both groups [40], as well as the underrepresentation of female cases as mentioned previously, particularly in countries with lower SDI levels.…”
Section: Rates Differences By Gender and Agementioning
confidence: 99%
“…Our study found a slightly higher decrease in ASPR and ASIR in females between 2019 and 1990, while similar changes in ASDR were observed between both genders. Most studies found in the literature reported higher rates of prevalence and incidence in males than females [28][29][30][31][32][33][34], while other studies reported no differences between males and females [24,[35][36][37], and some described that females had higher incidence and prevalence [35,38,39]. The disparities in reported rates between males and females in various studies may be due to varying risk factors distributions between both groups [40], as well as the underrepresentation of female cases as mentioned previously, particularly in countries with lower SDI levels.…”
Section: Rates Differences By Gender and Agementioning
confidence: 99%
“…Psoriasis is an immune-mediated skin disease that is estimated to affect 4.4% of the Portuguese population. 1 It can manifest at any age and imposes a significant burden on the patients due to its chronic nature, disfigurement, disability and associated comorbidities. 2,3 Major advances in immunological and genetic studies have identified IL-17 and IL-23 as key drivers in psoriatic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is estimated that approximately 400 000 people live with psoriasis in Portugal. 3 We discuss the case of a 54-year-old man with inconsistent follow-up for psoriasis for 15 years and who also had, depression and alcohol dependence with psychiatry followup, and was referred to social services due to financial issues causing poor therapy adherence. The patient presented to the emergency department with erythematous, scaly plaques sparing only the cervical and facial regions, with a high Psoriasis Area and Severity Index (PASI) of 65 (range 0-72) (Fig.…”
mentioning
confidence: 99%